SISTEM PELAYANAN WARGA CIKARANG UTAMA RESIDENCE BERBASIS WEB - Anita Sekar Rahayu; Hanum Putri Permatasari; Silvia Harlena; Amelia Belinda Silviana (Jurnal Ilmiah Teknik, 2024)
This study aims to determine how to create a service system for Cikarang Utama Residence residents. The process of delivering information about RT.052 environmental activities, information related to the RT management team, and services such as delivering criticism, suggestions and complaints are still carried out in a limited manner. Thus, a service information system was created that aims to serve the needs of Cikarang Utama Residence RT.052 residents. The research method used in creating this website is the SDLC method or (System Development Life Cycle), and programming languages to develop the system using HTML, PHP and MySQL as the database. The trial conducted using the blackbox method to ensure that the system can operate as expected, and to conduct browser comparison testing. In addition, a trial of the User Acceptance Test (UAT) method was carried out using a questionnaire. The hosting address of the citizen service system website created is https://pelayanan-warga.kesug.com/.